3D numerical modelling of shallow tunnel in weathered granite incorporating multi-stage excavation and pre-support - Yahya, S.M. (Penerbit UTM Press, 2016)
Generally tunnelling in urban ground condition is not always favourable due to the tunnelsâ susceptibility to major displacement especially when excavated in the soft soil and/or weak weathered rock formation. Apart from conventional support systems, pre-support measure like forepoling umbrella arch is frequently used to reinforce the ground. Modern computational tools allows the inclusion of multi-stage excavations and pre-support which was not possible in two dimensional (2D) plane strain. This paper demonstrates the three dimensional (3D) finite element analysis of Pahang-Selangor raw water transfer tunnel, as a reference case, where multi-stage excavation and pre-support are incorporated as intrinsic part of the model. The New Austrian Tunnelling Method (NATM)-3 segments which encountered Grade III weathered granite, having shallow overburden cover, was selected for numerical analysis using RS3 software. Comparison between simulated and observed data has shown good agreement during verification. Â© 2016 Penerbit UTM Press. All rights reserved.